Antibacterial activity of ginger essential oil derived nanobactericide against the growth of phytopathogenic bacteria - A Review - Mahesh Tiran Gunasena; Khairulmazmi Bin Ahmad; Mohd Zobir B Hussein; Asgar Ali; Mohd Zobir Syazwan Afif; Mohd Aswad bin Abdul Wahab (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2025)
Phytopathogenic bacteria infect various plants, causing economic losses, negative environmental consequences, and harming agricultural development. The most currently available antimicrobial agents for agriculture were potentially toxic, non-biodegradable, and cause significant harm to the ecosystem. As a result, novel, effective, safe, user-friendly, and alternative methods were urgently needed. Essential oils (EOs) have great potential in managing plant bacterial diseases because they successfully destroy various pathogenic bacteria. Ginger essential oil (GEO) is more widely used because it contains a diverse mixture of volatile substances, such as phenolic compounds, terpenes, polysaccharides, lipids, and organic acids. The antibacterial activity of the EO against phytopathogenic bacteria is significantly improved when it is converted into nanoparticles. Nanoparticles (NPs) that were derived from EOs have a considerable antibacterial action resulting from increased chemical solubility and consistency, minimal rapid evaporation, and slow depletion of the effective substances of EO. Ginger EOs were encapsulated in chitosan as a nanogel to improve the antibacterial effects and the consistency of the oils against pathogenic bacteria. Nanogel had been shown to amplify the antibacterial effect of EOs against pathogenic bacteria by enhancing their potential to disturb the integrity and permeability of the cell membranes. This paper focuses on three major parts of ginger essential oils: the antibacterial efficacy to control plant pathogenic bacteria, the possible mechanisms of action of essential oils as nanobactericides, and more importantly, the fabrication of bactericide nanoformulation.